Conclusions - Karapanos, Evangelos (My University, 2013)
The focus of Human-Computer Interaction has evolved from the study of the usability of interactive products towards a more holistic understanding of the psychological and social impact of products in people's lives. Firstly, this has resulted in a wealth of new concepts such as pleasure (Jordan, 2000), fun (Blythe et al., 2003), aesthetics (Tractinsky et al., 2000), and hedonic qualities in the use of personal interactive products (Hassenzahl, 2004), but also aspects of trust in online transactions (Egger, 2003), and the increased social connectedness that awareness systems bring among family members (IJsselsteijn et al., 2009; Markopoulos et al., 2004; Van Bel et al., 2008). Secondly, it has lead to an increased emphasis on methods for assessing the subjective quality and psychological consequences of product use. While a wealth of methods and techniques are available for assessing the usability of interactive products, research on methods for the subjective assessment of users' experiences is only at its infancy (e.g. Van Schaik and Ling, 2007; Fenko et al., 2009; Ben-Bassat et al., 2006; Zimmerman et al., 2009; Väänänen-Vainio-Mattila et al., 2008).
Keywords: Interactive Product; Personal Relevance; Repertory Grid; Empirical Insight; Interpersonal Diversity